Sequence-dependent effects in drug-DNA interaction: the crystal structure of Hoechst 33258 bound to the d(CGCAAATTTGCG)2 duplex. - Spink, N (1994)
The bis-benzimidazole drug Hoechst 33258 has been co-crystallized with the dodecanucleotide sequence d(CGCAAATTTGCG)2. The structure has been solved by molecular replacement and refined to an R factor of 18.5% for 2125 reflections collected on a Xentronics area detector. The drug is bound in the minor groove, at the five base-pair site 5'-ATTTG and is in a unique orientation. This is displaced by one base pair in the 5' direction compared to previously-determined structures of this drug with the sequence d(CGCGAATTCGCG)2. Reasons for this difference in behaviour are discussed in terms of several sequence-dependent structural features of the DNA, with particular reference to differences in propeller twist and minor-groove width.